Mysticism and Conflict: Amulets, Talismans, and the Enduring Bawku Chieftaincy Dispute in Ghana (1957-2022) - Bersong, Dennis Tibil; Awinbilla, Adamu Akudlil (Unisia, 2025)
Drawing on archival records, oral histories, and cultural artefacts, this article investigates how belief in the protective powers of amulets, talismans, charms, and other forms of African metaphysical social protection has shaped and sustained the protracted Bawku chieftaincy dispute between the Kusaas and Mamprusi from the late colonial era to the present. The study employs qualitative historical and ethnographic methods, combining colonial and postcolonial administrative documents with in‑depth interviews and detailed descriptions of ritual practices surrounding war garments, vanishing magic, and bodily fortification. The findings show that these spiritual‑material technologies do not merely accompany the conflict but actively influence decision‑making, risk‑taking, and attitudes toward violence, as many combatants perceive themselves as supernaturally shielded against bullets, blades, and other threats. This perceived immunity lowers fear of death, encourages offensive action, and weakens incentives to accept compromise or ceasefire, thereby undermining formal peacebuilding efforts led by governments, security forces, and civil society over more than six decades. Integrating insights from protection motivation theory, the article argues that amulets and talismans operate as culturally specific coping mechanisms that transform threat appraisal into a sense of control and empowerment, even in the face of repeated bloodshed. The study concludes that without explicitly engaging these metaphysical protection systems and their social meanings, interventions will continue to misdiagnose the roots of the Bawku conflict and risk reproducing the same ineffective outcomes.